Transfection efficiency and toxicity following delivery of naked plasmid DNA and cationic lipid-DNA complexes to ovine lung segments. - Emerson, M; Renwick, L; Tate, S; Rhind, S; Milne, E; Painter, H; Boyd, A; McLachlan, G; Griesenbach, U; Cheng, S; Gill, DR; Hyde, S; et al. (2003)
We defined, using a novel large animal model system, the acute pathologic response to localized pulmonary administration of either naked plasmid DNA (pDNA) or cationic lipid-pDNA complexes (pDNA:GL67) and related such responses to concomitant indicators of transfection efficiency, namely levels of chloramphenicol acetyl transferase (CAT) protein and mRNA in specific lung tissue compartments. We instilled doses of 0.2, 1, and 5 mg pDNA to spatially distinct lung segments in six anesthetized sheep and doses of 0.2, 1, and 5 mg pDNA:GL67 to a further six sheep. Twenty-four hours after gene delivery the sheep were euthanized and necropsy examination with sampling of relevant tissues was carried out. Levels of plasmid-derived CAT-specific mRNA and CAT protein in samples derived from segments treated with either pDNA or pDNA:GL67 increased in relation to the administered dose. Levels of mRNA and protein expression were greater for pDNA:GL67 than for pDNA alone. A significant correlation was observed between mRNA and protein expression in samples derived from airways treated with pDNA:GL67. Histopathological changes following administration of both pDNA and pDNA:GL67 were characterized by a neutrophilic inflammation predominantly oriented on airways. The severity of the inflammatory response appeared to correlate with the administered dose of DNA and was generally more severe for pDNA:GL67.